Making waves: How to improve scholarly impact performance through stakeholder engagement - Herman Aguinis; Bria C. Gibson (BRQ Business Research Quarterly, 2025)
Most scholarly impact measures focus exclusively on an essential but single group of stakeholders: other researchers. However, business research aims to benefit not only other researchers (i.e., internal) but also additional (i.e., external) stakeholders. Accordingly, we offer an expanded multidimensional and multistakeholder conceptualization of scholarly impact that includes the following dimensions and their stakeholders: (1) personal (i.e., individual researchers), (2) theory and research (i.e., other researchers), (3) educational (i.e., students, parent institutions, and university community), (4) organizational (i.e., practitioners including managers, consultants, and industry), (5) societal (i.e., media, policymakers, governments, and nongovernmental organizations), and (6) global (i.e., international institutions). We also describe scholarly impact measures across these dimensions and stakeholders. Then, we extend the capacity, opportunity, and relevant exchanges (CORE) performance model to describe the construct of scholarly impact performance (SIP) and provide actionable recommendations that individuals and organizations can implement to enhance SIP across institutional contexts (i.e., research-intensive, teaching-oriented, and those in emerging countries). In sum, we offer a broader conceptualization of scholarly impact, measures, and recommendations for incentivizing and enhancing SIP.
Keywords: A10; A13; D02; D21; F60; I20; I23; I26; L2; 650; Scholarly impact; research performance; scholarly impact performance; CORE performance model; stakeholder engagement; stakeholder theory; research-practice gap